Knowledge sharing: Improving the central component of knowledge management - Haji, M. (Cranfield University, 2006)
This thesis project has sought to investigate the major factors affecting knowledge sharing in organisations. Research into existing studies and findings from an industrial survey highlighted that there are major areas of concern, these were: - The lack of management emphasis; - The challenge of culture; and - Determining what knowledge should be shared. Investigations into four case studies and discussions with their knowledge managers identified that different approaches and activities were been employed; these ranged from those that focused on technology to those that focused on people. To help organisations develop a holistic approach and in turn increase their chances of improving knowledge sharing the author has developed a set of guidelines directing organisation to focus their efforts on four key areas; strategy, people, process and technology. Each focus area proposes a range of guidelines; where within each are directions detailing what’s involved, why it is important, how it is carried out and when. The guidelines were packaged onto an internet based framework and were evaluated by a range of industrial practitioners, of which the results are discussed. The theory and main themes of the project have been outlined and the results from the industrial survey and case study investigations have been analysed.